2021
DOI: 10.3171/2020.8.jns202280
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of intrahospital transport on cerebral metabolism in patients suffering severe aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Intrahospital transport for CT scans is routinely performed for neurosurgical patients. Particularly in the sedated and mechanically ventilated patient, intracranial hypertension and blood pressure fluctuations that might impair cerebral perfusion are frequently observed during these interventions. This study quantifies the impact of intrahospital patient transport on multimodality monitoring measurements, with a particular focus on cerebral metabolism. METHODS Forty intrahospital transports in 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In other words, the definitions of secondary brain injuries are limited by the number of available modalities. For example, Lindner et al (2021) defined mitochondrial dysfunction (single modality) as: CMD lactate/pyruvate (L/P)-ratio ≥ 40 + CMD-pyruvate ≥ 70 μmol/L, whereas Khellaf et al defined mitochondrial dysfunction (three modalities) as: CMD L/P-ratio>25 for more than 2 h, ICP <20 mmHg; PbtO 2 <15 mmHg; PRx <0.3; brain extracellular glucose >1 mmol/L (Khellaf et al, 2022).…”
Section: Results Objective Ii: Secondary Injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the definitions of secondary brain injuries are limited by the number of available modalities. For example, Lindner et al (2021) defined mitochondrial dysfunction (single modality) as: CMD lactate/pyruvate (L/P)-ratio ≥ 40 + CMD-pyruvate ≥ 70 μmol/L, whereas Khellaf et al defined mitochondrial dysfunction (three modalities) as: CMD L/P-ratio>25 for more than 2 h, ICP <20 mmHg; PbtO 2 <15 mmHg; PRx <0.3; brain extracellular glucose >1 mmol/L (Khellaf et al, 2022).…”
Section: Results Objective Ii: Secondary Injuriesmentioning
confidence: 99%
“…For example, Hosmann et al (2022) define indications for cerebral ischemia as CMD L/P-ratio >40 CMD-glycerol >100 μmol/L, CMD-lactate >4 mmol/L, whereas Nyholm et al (2017) defined cerebral ischemia as CMD-L/P ratio >40 and CMD-pyruvate <50 mol/L). For brain tissue hypoxia monitored by PbtO 2 there were in general two definitions used: PbtO 2 <15 mmHg ( Burnol et al, 2021 ; Hosmann et al, 2021 ) or <20 mmHg ( Le Roux et al, 2014 ; Gagnon et al, 2020 ; Sekhon et al, 2020 ; Gouvea Bogossian et al, 2021 ).…”
Section: Results Objective Ii: Secondary Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CVS at the ICU reflect a highly vulnerable subgroup of SAH patients who are at risk for DCI that may develop when cerebral blood supply decreases below demand. An invasive diagnostic and therapeutic management in patients with critically low cerebral blood supply may lead to varying blood pressure and decreased monitoring compared to the treatment at the ICU over a period of time, which may explain why the otherwise effective treatment of angiographic CVS does not translate into better outcomes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to directly attributable complications, any kind of intrahospital transport for diagnostics and intervention bears the risk of transport-related complications, e.g., drop in blood pressure and lowering of blood supply below demand, resulting in ischemia. Furthermore, Hosmann et al [ 10 ] found detrimental effects of intrahospital transports on cerebral metabolism in patients with SAH, leading to sustained impaired neuronal metabolism for several hours. The authors concluded that any kind of intrahospital transport for neuro-imaging should strongly be reconsidered and only indicated if the expected benefits outweigh the risks.…”
Section: Discussionmentioning
confidence: 99%